Developing a Framework for Understanding the Personal Motivations of Sustainability Leaders - Horn, Jennifer Licad (Archīum Ateneo, 2020)
This study explores the initial and sustaining motivations that drive leaders to pursue sustainability as a profession or vocation. Exploratory interviews were conducted with 16 sustainability leaders in the Philippines working in sectors ranging from corporate to social enterprise, NGO, and academia. Findings from thematic analysis reveal significant life experiences that drive initial motivation, how feedback sustains motivation, and the importance of self-awareness and positive psychological factors in starting and sustaining their work or advocacy. A framework for understanding motivations is developed therein, drawing on themes extracted from the interviews, Stern’s Value-Belief-Norm Theory, and Authentic and Transformational Leadership theories. Recommendations are given on how motivation can be instigated and sustained, namely, by cultivating hope and other positive psychological factors, integrating experiential learning to develop awareness, connectedness, and empathy, and creating social support and enabling environments. Further research to develop an instrument for measuring sustainability leadership motivation, one that can inform sustainability education facilitators of the effectiveness of their programs in inspiring participants to take action, is also recommended.